Resolution of Brainstem Edema after Neurosurgical Occlusion of Dural Arteriovenous Fistulas of the Craniocervical Junction: Report of Three Cases and Review - Firsching, Raimund; Kohl, Jana; Skalej, Martin; Beuing, Oliver (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective Dural arteriovenous fistulas of the craniocervical junction are rare but the most dangerous of spinal fistulas. The concurrent brainstem edema has been attributed to increased pressure within the venous outflow of the brainstem and upper cord, but the differential diagnosis of brainstem edema is demanding. This report presents the details of clinical findings, magnetic resonance imaging (MRI) , surgical techniques, and follow-up of these fistulas.Methods Three cases with dural arteriovenous fistulas and edema of the brainstem and upper cord are described plus a review of the literature. Clinical presentation, radiologic findings, and a follow-up of outcomes are presented.Results All three cases with misleading diagnoses at the time of referral experienced variable degrees of tetraparesis with brainstem edema on MRI. Congested veins on MRI raised the suspicion of a vascular origin of the edema. The diagnosis was established with highly specific angiography with microcatheters identifying a feeder from the ascending pharyngeal artery in two cases and a tentorial feeder from the carotid artery in one case. The operation included temporary clipping of the fistula and neuromonitoring. Follow-up confirmed improvement of clinical signs and resolution of the brainstem edema on MRI.Conclusion Edema of the brainstem and cervical cord may be caused by a dural arteriovenous fistula of the craniocervical junction. Surgical occlusion may be an efficient option for the complete resolution of radiologic and clinical symptoms.
Keywords: brainstem edema; craniocervical junction; dural fistula; arteriovenous malformation